Funeral contexts associated to the Ushnu in the Archaeological Complex of Lumbra, middle valley of the Chancay-Huaral river - Dalen Luna, Pieter D. van (2018)
The present article presents the finding of funerary contexts found in association with ushnu, in sector B of the archaeological complex of Lumbra. This archaeological complex is the only one in the Chancay-Huaral valley, where Tawantinsuyu architectural elements such as the Ushnu and the two kanchas have been identified in front of the square. The finding of these two funerary contexts shows new insights for the understanding of the Tawantinsuyu occupation in the middle valley of the Chancay-Huaral river.